Availability of literature on engineering ethics in the Internet - Ismail, Yusof; Sarif, Suhaimi Mhd (IIUM Press, 2011)
Internet is becoming a popular tool among career oriented people. Among professionals, some of the engineers use the Internet in their work to search for information. The study is carried out to ascertain comparative availability of the materials on ethics and engineers in four top Internet search engines (ISE’s). Three ISE’s were accessed on 2 February 2011, from 2.21 p.m. to 4.21 p.m. [Gombak Time] using a combination of selected search terms: education, engineer, engineering, ethics, Islam, professional, research, and training. The search results or hits produced by the selected ISE’s were analyzed using a specially created instrument/format. The study computes relative ratios of the coverage of selected terms in relation to the number of hits for selected terms within each ISE. The ratios are obtained by dividing the hits for a search term or combination into the total hits within each ISE. The results of the analysis reveal the ISE’s that contain the highest frequency of materials on engineers and ethics. The findings suggest to engineering students and practitioners of varying capabilities among the ISE’s used in the study to learn about engineering ethics. Limitations of the study and suggestions for further research are included in the study.